2004
DOI: 10.2527/2004.823705x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytase addition and dietary calcium and phosphorus levels on plasma metabolites and ileal and total-tract nutrient digestibility in pigs1,2,3,4

Abstract: Two experiments were conducted to determine the effect of phytase on plasma metabolites and AA and energy digestibility in swine. In Exp. 1, eight barrows (surgery BW = 52 kg) were fitted with steered ileocecal cannulas. The experiment was a Latin rectangle and the treatments were 1) corn-soybean meal diet adequate in Ca and P (0.5% Ca, 0.19% available P [aP]), 2) corn-soybean meal diet with reduced Ca and P (0.4% Ca, 0.09% aP), 3) Diet 1 with 500 phytase units/kg, or 4) Diet 2 with 500 phytase units/kg. Pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
31
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 31 publications
10
31
0
1
Order By: Relevance
“…In the present study, the effect of dietary CaP supply by adding different amounts of monocalcium phosphate has been studied. The increase in ATTD of P by adding a higher amount of dietary inorganic P was expected and is in agreement with other studies(Johnston et al, 2004;Stein, Kadzere, Kim, & Miller, 2008), and thereby increasing P availability for the microbes. However, the P digestibility might be negatively affected due to the formation of insoluble Ca-InsP 6 complexes and the entailed limited efficiency of mucosal phytase, in particular in the proximal gut.…”
supporting
confidence: 92%
“…In the present study, the effect of dietary CaP supply by adding different amounts of monocalcium phosphate has been studied. The increase in ATTD of P by adding a higher amount of dietary inorganic P was expected and is in agreement with other studies(Johnston et al, 2004;Stein, Kadzere, Kim, & Miller, 2008), and thereby increasing P availability for the microbes. However, the P digestibility might be negatively affected due to the formation of insoluble Ca-InsP 6 complexes and the entailed limited efficiency of mucosal phytase, in particular in the proximal gut.…”
supporting
confidence: 92%
“…They estimated that 500 U of phytase added per kilogram of diet to a 10% CP diet could replace 1.01 percentage units of CP. Johnston et al (2004) observed an improvement in AA AID when phytase was added to the diet and dietary Ca and P concentrations were reduced but observed no effect of phytase on N AID. Variations in phytase equivalency values for CP reported in recent reports (reviewed by Adeola and Sands, 2003) occur because of differences in the basal CP content of the diet, differences in the concentration of phytate P and inorganic P in the diet, differences in the Ca:P ratio, and differences in the grain feedstuffs used in the basal diets.…”
Section: Discussionmentioning
confidence: 88%
“…Kemme et al (1995) reported an increase in ileal digestibility of AA, and Jongbloed et al (1995) and Christensen and Nielsen (1995) demonstrated an increase in apparent total tract digestibility (ATTD) of N. However, Lantzsch and Drochner (1995) showed no improvement in N digestibility when microbial phytase was added to the diets of breeding sows. More recently, Johnston et al (2004) reported a 4.4% increase in average AA digestibility, when 500 U/kg of phytase were added and Ca and P levels were each reduced by 0.10 percentage units. However, in a review, Adeola and Sands (2003) caution against the use of an equivalency value of microbial phytase from AA due to inconsistencies in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…2005). Johnston et al . (2004) fed a diet with available P reduced by 0.12% units to growing pigs, and concluded that the combination of P reduction and phytase addition increased nutrient digestibility.…”
Section: Discussionmentioning
confidence: 93%
“…1997; Sands et al . 2001; Johnston et al . 2004) and pea‐containing diets supplemented with enzyme (Nyachoti et al .…”
Section: Discussionmentioning
confidence: 99%